2020 European Conference on Optical Communications (ECOC) 2020
DOI: 10.1109/ecoc48923.2020.9333193
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Metasurface Building Blocks for Arbitrary On-chip High-order Mode Manipulation

Abstract: On-chip integrated mode-division multiplexing (MDM) has been emerging as a promising technology to further improve the link capacity and satisfy the continuously increasing bandwidth demand in data communications. One of the most important components in MDM and multimode photonics is a mode converter. While several configurations have been developed to realize on-chip mode converters, it is still very challenging to achieve versatile high-order mode converters with high performance in a generic way to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previously, we have demonstrated that a single dielectric slot can function as a power splitter and a phase shifter simultaneously 33 , which inspires the implementation of beam shaping principle completely with metamaterial BBs consisting of fully etched dielectric slots (more information about the origin of metamaterial BBs is provided in Supplementary Note 1 ). Considering the symmetry property of electric field profiles of eigenmodes, the TE 0 -TE 2 metamaterial BB 38 is designed with a symmetric arrow-like shape, as depicted in Fig. 1c .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that a single dielectric slot can function as a power splitter and a phase shifter simultaneously 33 , which inspires the implementation of beam shaping principle completely with metamaterial BBs consisting of fully etched dielectric slots (more information about the origin of metamaterial BBs is provided in Supplementary Note 1 ). Considering the symmetry property of electric field profiles of eigenmodes, the TE 0 -TE 2 metamaterial BB 38 is designed with a symmetric arrow-like shape, as depicted in Fig. 1c .…”
Section: Resultsmentioning
confidence: 99%